2004
DOI: 10.1177/0898264304268586
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and Depressive Symptoms as Predictors of Home Help Utilization Among the Oldest Old

Abstract: Improvement of screening activities for public home help needs of community-dwelling elders might allow better targeting of limited social resources to the most needy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 40 publications
(42 reference statements)
1
22
0
1
Order By: Relevance
“…The stable proportion indicated that use of home help was not influenced by proximity to death, and the regression analysis confirmed that increasing chronological age raised the likelihood of using home help by 6% per year. Previous studies of this study population have shown that needsrelated factors such as limitations in activities of daily living or dementia were the main determinants of home help utilisation, both at a certain point in time (Larsson et al 2004) and over a longer time period (Larsson et al 2006). The stable percentage of home help recipients may thus be explained by the onset of general frailty in advanced age, and an associated long-standing need for assistance with household chores and personal care in order to 'age in place'.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The stable proportion indicated that use of home help was not influenced by proximity to death, and the regression analysis confirmed that increasing chronological age raised the likelihood of using home help by 6% per year. Previous studies of this study population have shown that needsrelated factors such as limitations in activities of daily living or dementia were the main determinants of home help utilisation, both at a certain point in time (Larsson et al 2004) and over a longer time period (Larsson et al 2006). The stable percentage of home help recipients may thus be explained by the onset of general frailty in advanced age, and an associated long-standing need for assistance with household chores and personal care in order to 'age in place'.…”
Section: Discussionmentioning
confidence: 79%
“…There are no explicit rules for how much home help a person is entitled to, given the degree of dependency. Besides ADL limitations and dementia, living alone is found to be the most important predictor of receiving home help services, as well as care in institutional care facilities (Larsson et al 2004(Larsson et al , 2006. Home help facilitates the day-to-day life of older people, thereby enabling them to stay in their own homes for as long as possible.…”
Section: Introductionmentioning
confidence: 99%
“…functional or cognitive capacity (RIS MRC CFAS, 1998;Wimo et al, 2002), providing opportunities to analyse the patterns of how resources are utilized. Others have studied predictors of home help utilization restricted to whether the subjects did or did not receive public home help rather than the number of hours of help received (Larsson et al, 2004). Although there are several studies describing the amount of formal and informal care, most of these studies have included selected populations such as clinical samples or convenient samples (Schneider et al, 2002;Wimo et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Others have studied predictors of home help utilization restricted to whether the subjects did or did not receive public home help rather than the number of hours of help received (Larsson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%